1991
DOI: 10.1080/07391102.1991.10507891
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Selective Binding to the DNA Major Groove: Tris(1,10-phenanthroline) Metal Complexes Binding to Poly(dG-dC) and Poly(dA-dT)

Abstract: Molecular modelling and energy minimisation calculations that incorporate solvent effects have been used to investigate the complexation of delta and lambda-[Ru(1,10-phenanthroline]2+ to DNA. The most stable binding geometry for both enantiomers is one in which a phenanthroline chelate is positioned in the major groove. The chelate is partially inserted between neighbouring base pairs, but is not intercalated. For delta, though not for lambda, a geometry with two chelates in the major groove is only slightly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 8 publications
4
77
0
Order By: Relevance
“…These changes are typical of a complex bound to DNA through intercalation involving insertion of the aromatic chromophore of the diimine ligands in between the base pairs of DNA. As the extent of hypochromism is commonly consistent with the strength of intercalative interaction [48][49][50], the observed trend in hypochromism, 3 > 2 > 1 reflects the trend in DNA-binding affinities of the complexes. From the observed spectral changes the value of the intrinsic equilibrium DNA-binding constant K b was determined by regression analysis using Eq.…”
Section: Absorption Spectral Studiesmentioning
confidence: 73%
“…These changes are typical of a complex bound to DNA through intercalation involving insertion of the aromatic chromophore of the diimine ligands in between the base pairs of DNA. As the extent of hypochromism is commonly consistent with the strength of intercalative interaction [48][49][50], the observed trend in hypochromism, 3 > 2 > 1 reflects the trend in DNA-binding affinities of the complexes. From the observed spectral changes the value of the intrinsic equilibrium DNA-binding constant K b was determined by regression analysis using Eq.…”
Section: Absorption Spectral Studiesmentioning
confidence: 73%
“…17 However, possibility of classic intercalation of any phenanthroline ligands has been ruled out by viscosity measurements. 16 Although partial intercalation from the major groove was suggested by molecular modeling and energy minimization work, 18 a recent NMR and circular dichroism study showed that the interaction between the [Ru(phen) 2 …”
Section: +mentioning
confidence: 99%
“…The propeller-like ruthenium tris-phenanthroline complexes do show differential binding between A-T and G-C sequences [2] and moreover may exhibit a preference for purine 3', 5' pyrimidine sites in DNA [3]. Perhaps the most intriguin starting point for a molecule upon which to build nucleic acid selectivity is the ubiquitous sper-mine.…”
Section: Dna As Targetmentioning
confidence: 99%
“…At their lowest level the contributions represent the replacement of crude mechanical models by displays of structure which are a much more accurate reflection of molecular reality capable of demonstrating motion and solvent effects [1][2][3]. Beyond this, theoretical calculations permit the computation of binding free energies and other relevant molecular properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation